Analisis Regresi Linier Berganda Pada Faktor yang Berpengaruh Terhadap Motivasi Kerja Karyawan - Theofani, Gracia; Sediyono, Eko (Sinkron : jurnal dan penelitian teknik informatika, 2022)
This study aims to analyze the factors that influence employee motivation at PT XYZ. The analysis was carried out using four variables, namely Facilities, Work Environtment, Salary and Jobdesk. In collecting data, this study used primary and secondary data. Primary data were collected by distributing questionnaires to employees at PT XYZ using the Voluntary Sampling Technique, questionnaires were distributed to employees with a willingness to participate in the research. From the questionnaire obtained 71 data as primary data. Secondary data used results of previous studies and data from PT XYZ which was given to assist the research. Furthermore, data processing is done by using multiple linear regression algorithm. The data is processed and analyzed using the RStudio software. Parameter significance test and classical assumption test performed with RStudio. From this research, it is concluded that the variables that have the most influence on employee motivation at PT XYZ are Facilities and Jobdesk, where these variables have a positive effect on employee motivation at PT XYZ. The results of the analysis show that an increase in facilities will increase work motivation by 20,659% and jobdesk will increase work motivation by 27,901%. This research is expected to be the company's decision in its efforts to increase employee motivation.